Трапецієвидна дифракційна антена - Болтаєва, К. У. (ХНУРЕ, 2021)
The structure of diffraction antenna based on the trapezoidal elements is considered. The model of the antenna was developed and experimental setup has been assembled. Experimental studies of the trapezoidal diffraction antenna have been carried out.
Keywords: дифракційна антена; мікросмужкова антена